Does attenuated skin blood flow lower sweat rate and the critical environmental limit for heat balance during severe heat exposure?. Issue 2 (26th December 2016) - Cramer, Matthew N.; Gagnon, Daniel; Crandall, Craig G.; Jay, Ollie
Abstract : New Findings: What is the central question of this study? Does attenuated skin blood flow diminish sweating and reduce the critical environmental limit for heat balance, which indicates maximal heat loss potential, during severe heat stress? What is the main finding and its importance? Isosmotic hypovolaemia attenuated skin blood flow by ∼20% but did not result in different sweating rates, mean skin temperatures or critical environmental limits for heat balance compared with control and volume‐infusion treatments, suggesting that the lower levels of skin blood flow commonly observed in aged and diseased populations may not diminish maximal whole‐body heat dissipation. Attenuated skin blood flow (SkBF) is often assumed to impair core temperature ( T c ) regulation. Profound pharmacologically induced reductions in SkBF (∼85%) lead to impaired sweating, but whether the smaller attenuations in SkBF (∼20%) more often associated with ageing and certain diseases lead to decrements in sweating and maximal heat loss potential is unknown. Seven healthy men (28 ± 4 years old) completed a 30 min equilibration period at 41°C and a vapour pressure ( P a ) of 2.57 kPa followed by incremental steps in P a of 0.17 kPa every 6 min to 5.95 kPa. Differences in heat loss potential were assessed by identifying the critical vapour pressure ( P crit ) at which an upward inflection in T c occurred. The following three separate treatments elicited changes in plasma volume to achieve three distinct levels of SkBF: control (CON); diuretic‐induced isosmotic dehydration to lower SkBF (DEH); and continuous saline infusion to maintain SkBF (SAL). The T c, mean skin temperature ( T sk ), heart rate, mean laser‐Doppler flux (forearm and thigh; LDFmean ), mean local sweat rate (forearm and thigh; LSRmean ) and metabolic rate were measured. In DEH, a 14.2 ± 5.7% lower plasma volume resulted in a ∼20% lower LDFmean in perfusion units (PU) (DEH, 139 ± 23 PU; CON, 176 ± 22 PU; and SAL, 186 ± 22 PU; P  = 0.034). However, LSRmean and whole‐body sweat losses were unaffected by treatment throughout ( P  > 0.482). The P crit for T c was similar between treatments (CON, 5.05 ± 0.30 kPa; DEH, 4.93 ± 0.16 kPa; and SAL, 5.12 ± 0.10 kPa; P  = 0.166). Furthermore, no differences were observed in the skin‐air temperature gradient, metabolic rate or changes in T c ( P  > 0.197). In conclusion, a ∼20% reduction in SkBF alters neither sweat rate nor the upper limit for heat loss from the skin during non‐encapsulated passive heat stress. Abstract :